2021
DOI: 10.1039/d1ra00221j
|View full text |Cite|
|
Sign up to set email alerts
|

Exploration of the cofactor specificity of wild-type phosphite dehydrogenase and its mutant using molecular dynamics simulations

Abstract: Phosphite dehydrogenase (Pdh) catalyzes the NAD-dependent oxidation of phosphite to phosphate with the formation of NADH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The binding energy between T379L/A380 M and ATP was −14.34 kcal/mol, which was lower than that of WT-AK (−6.5 kcal/mol) in the 100 ns simulation process ( Fig. 5 B) [ 17 ]. Owing to the lower binding energy indicating stronger binding ability [ 18 ], T379L/A380 M had stronger binding affinity for ATP than WT-AK.…”
Section: Resultsmentioning
confidence: 99%
“…The binding energy between T379L/A380 M and ATP was −14.34 kcal/mol, which was lower than that of WT-AK (−6.5 kcal/mol) in the 100 ns simulation process ( Fig. 5 B) [ 17 ]. Owing to the lower binding energy indicating stronger binding ability [ 18 ], T379L/A380 M had stronger binding affinity for ATP than WT-AK.…”
Section: Resultsmentioning
confidence: 99%
“…The root‐mean‐square deviation (RMSD) is generally used to describe the fluctuation and measure the average change of the enzyme/ligand complex [21] . The distributions of the relative frequency of the RMSD values intuitively reflects the stability of the enzyme/ligand complexes [22] . The RMSD values of Mu0_NADPH could be stabilized at approximately 1.5 Å in the 50 ns (Figure 3a–3b).…”
Section: Resultsmentioning
confidence: 99%
“…[21] The distributions of the relative frequency of the RMSD values intuitively reflects the stability of the enzyme/ligand complexes. [22] The RMSD values of Mu0_NADPH could be stabilized at approximately 1.5 Å in the 50 ns (Figure 3a-3b). It is indicated that the protein backbone of Mu0 showed a stable conformation when NADPH is bound to the cofactor-binding site.…”
Section: Structure-guided Cofactor Specificity Engineering Of Lfsdr1mentioning
confidence: 95%
“…Interestingly, only four of the 18 mutant strains showed significantly enhanced PtxD activity ( Supplementary Figure S3 , Table 1 ), which indicated the critical function of the 139th site for phosphite binding or oxidizing potential. X-ray crystallographic analysis revealed that PtxD has two catalytic domains ( Liu et al, 2019 ; Liu et al, 2021 ). Molecular modeling of the PtxD R4506 protein shows that the 139th tyrosine of PtxD R4506 locates in a random coil connecting two catalytic domains ( Supplementary Figure S8A ).…”
Section: Discussionmentioning
confidence: 99%
“…The better profiles of PtxD R4506 have attracted increasing attention in the biotechnological field. Most recently, some properties of PtxD R4506 , such as cofactor specificity, thermostablity, and organic solvents tolerance, have been evolved by several groups ( Liu et al, 2019 ; Abdel-Hady et al, 2021 ; Liu et al, 2021 ). However, to the best of our konwledge, there is no report on the improvement of PtxDR 4506 catalytic efficiency, which is also extremely important for its application.…”
Section: Introductionmentioning
confidence: 99%